THE EFFECT OF MOTIVATION AND JOB COMPETITION ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE AT RSUD TUANKU IMAM BONJOL, LUBUK SIKAPING - Pelda Harianti; Novi Yanti; Yulistia; Agus Sutardjo; Dina Adawiyah (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the effect of motivation and job competition on employee performance through job satisfaction as an intervening variable among nursing staff at RSUD Tuanku Imam Bonjol, Lubuk Sikaping. The population consisted of 183 nursing employees, with a sample of 64 respondents determined using the Slovin formula. Data were collected through a closed questionnaire using a 1–5 Likert scale and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square with SmartPLS version 4. The results show that job competition has a positive and significant effect on both job satisfaction and employee performance, while motivation has a positive but not significant effect on either variable. Job satisfaction also has a positive but not significant effect on employee performance. In the indirect-effect testing, motivation has a positive and significant effect on employee performance through job satisfaction, whereas job competition has a positive but not significant effect on employee performance through job satisfaction. These findings indicate that healthy job competition is a more dominant factor than motivation in driving the satisfaction and performance of nursing staff.